Giant left coronary artery with coronary cameral fistula in significant coronary artery disease : A case report - Caesario, Fahreza; Handari, Saskia Dyah (Heart Science Journal, 2025)
Background : Coronary Artery Fistula are coronary anomalies that affected populations with rare incidences. Concomitant disease such as coronary artery disease (CAD) may be occurred in CAF and causing complexity to its management. Objective : This case presentation aimed to describe the characteristic, diagnosis and management of CAF with concomitant disease such as CAD. Case Presentation : We will discuss A 56 year old male admitted as an outpatient with left sided chest pain as the chief complain. The chest pain was described as ischemic chest pain with supporting examination lead to the suspicion of coronary artery disease.  Contrast enhanced CT Angiography examination was planned for diagnosing Coronary Artery Disease in this patient. 3D reconstruction of the coronary tree revealed giant LAD (Diameter 6.5 – 7mm) with normal size of LCx and Dominant RCA. The distal LAD was communicating with the LV cavity through big coronary fistulae. Impression of significant stenosis showed in the proximal RCA described as mixed plaque causing >70% Stenosis. PCI of the RCA and CAF Closure management was proposed but there was a disagreement of further coronary intervention from the patient. Conclusion : CAF in concomitant CAD is a complex structural disease with challenging management. Combination of surgical procedure was the recommendation for the management of this case.